High‐Resolution Electronic Excitation and Emission Spectra of Pentacene and 6, 13‐Diazapentacene Monomers and Weakly Bound Dimers by Matrix‐Isolation Spectroscopy. Issue 6 (22nd December 2020) - Thusek, Jean; Hoffmann, Marvin; Hübner, Olaf; Germer, Stefan; Hoffmann, Hendrik; Freudenberg, Jan; Bunz, Uwe H. F.; Dreuw, Andreas; Himmel, Hans‐Jörg
Abstract: N‐Heteropolycycles are among the most promising candidates for applications in organic devices. For this purpose, a profound understanding of the low‐energy electronic absorbance and emission characteristics is of crucial importance. Herein, we report high‐resolution absorbance and fluorescence spectra of pentacene (PEN ) and 6, 13‐diazapentacene (DAP ) in solid neon obtained using the matrix‐isolation technique. Accompanying DFT calculations allow the assignment of specific vibrationally resolved signals to corresponding modes. Furthermore, we present for the first time evidence for the formation of van der Waals dimers of both substances. These dimers exhibit significantly different optical characteristics resulting from the change of electronic properties evoked by the incorporation of sp 2 nitrogen into the molecular backbone. Abstract : High‐resolution and fluorescence spectra of pentacene and 6, 13‐diazapentacene isolated in solid neon are presented. In alliance with quantum‐chemical calculations, the spectra give valuable information about the monomeric compounds. In addition, the matrix‐isolation technique was used to generate weakly bound dimers which were spectroscopically studied for the first time, providing information about the electronic coupling therein.